An empirical assessment of tourist loyalty towards budget accommodation service / Tintin Suhaeni ... [et al.] - Suhaeni, Tintin; Setiawati, Lina; Setiawardani, Maya; Suhartanto, Dwi (Universiti Teknologi Mara Selangor, 2019)
Hotel industry as a provider of tourist accommodation is an important component in the tourism industry. This study was designed to identify how domestic tourists develop loyalty towards budget accommodation. Referring to the existing literature, three predictors are included in the model of loyalty: service quality, service value, and customer satisfaction. The data were collected from 298 domestic tourists in West Java Province, Indonesia. The findings indicate that tourists tend to be not loyal to budget accommodation. Further, tourists’ perception on the service quality, perceived value, and satisfaction are still not as expected. In terms of how domestic tourists develop loyalty, this study underlines the importance of service quality and customer satisfaction. Although these three loyalty drivers are important in determining tourist loyalty towards a budget accommodation service provider, this study also highlights the effect of service quality on loyalty, value, as well as guest satisfaction.